An -Firm Real-Time Aware Fault-Tolerant Mechanism in Wireless Sensor Networks - Bijun Li; Ki-Il Kim (International Journal of Distributed Sensor Networks)
Many real-time routing mechanisms have been proposed to support the newly developed wireless sensor networks (WSNs) applications such as the transmission and retrieval of multimedia traffic. However, the inherent source constraints of sensor network and instability of wireless communication set quite a problem for the existing routing mechanisms to meet the quality of service (QoS) requirements of some specific QoS-aware applications. Hence, real-time fault-tolerant schemes are highly desired for WSNs to address these challenges. In this paper, we propose an ( m , k ) -firm-based real-time fault-tolerant mechanism, which helps routing mechanisms to achieve specific QoS requirement by employing a local status indicator (LSI) at each sensor node to monitor and evaluate the local conditions of node and network. Therefore, specific fault recovery mechanisms could be implemented for ensuring an acceptable QoS performance, according to the evaluated LSI values. By using this fault-tolerant scheme, each node dynamically adjusts its transmission capability to mitigate the performance degradation of real-time service caused by network faults and to maintain the desired reliability and timeliness. Simulation result shows that LSI cannot only help to reduce the effects of congestion, link failure, and void, but also reach higher successful transmission ratio and smaller transmission delay.